Do the 4Ps of marketing mix strategy assuage fears of travelling - Kai Xin Tay; Jennifer Kim Lian Chan; Diana Mohamad (ResearchGate, 2023)
This study examines the marketing mix that is required to decrease travel fears (TF) and increase travel intentions (TI) after the lifting of COVID-19 travel restrictions. It also investigates the mediating effect of TF on the marketing mix strategy to increase TI as well as the moderating effect of gender and employment status on the correlations of the developed model. Structural equation modelling was used to analyse 1830 survey responses. The findings indicate that there are only product-based marketing mix strategies decrease TF and increase TI while promotion-based strategies have the opposite effect. TF were found to mediate the effect of product- and promotion-based strategies on TI while gender and employment status had little effect on the direct correlations and mediating effects of the developed model. The conventional marketing mix strategy; specifically, price- and place-based strategies; are no longer relevant in the current context of the COVID-19 pandemic.